2016
DOI: 10.1016/j.electacta.2016.10.097
|View full text |Cite
|
Sign up to set email alerts
|

Mass transport and active area of porous Pt/Ti electrodes for the Zn-Ce redox flow battery determined from limiting current measurements

Abstract: The conversion of soluble cerium redox species in the zinc-cerium redox flow battery and other electrochemical processes can be carried out at planar and porous platinised titanium electrodes.The active area, current density, mass transfer coefficient and linear electrolyte flow velocity through these structures have a direct influence on the reaction yield and the relationship between cell potential and operational current density during charge and discharge of a flow battery. A quantitative and practical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 50 publications
3
78
0
Order By: Relevance
“…Additionally, increasing flow rate increases the limiting current density for the cell, again due to improved mass transfer in the porous electrode. This behavior is anticipated from prior experimental reports, 17,18,23,28 as well as our model, which indicates that faster mass transfer rates (smaller θ) lead to improved electrochemical performance. Figure 6b illustrates another trend previously reported in literature, 45 where increasing the active material concentration for one field (SFF) at a fixed flow rate (2 mL min −1 ) alleviates cell polarization despite a decrease in electrolyte conductivity ( Figure 5).…”
Section: Experimental Results and Model Fittingsupporting
confidence: 86%
See 4 more Smart Citations
“…Additionally, increasing flow rate increases the limiting current density for the cell, again due to improved mass transfer in the porous electrode. This behavior is anticipated from prior experimental reports, 17,18,23,28 as well as our model, which indicates that faster mass transfer rates (smaller θ) lead to improved electrochemical performance. Figure 6b illustrates another trend previously reported in literature, 45 where increasing the active material concentration for one field (SFF) at a fixed flow rate (2 mL min −1 ) alleviates cell polarization despite a decrease in electrolyte conductivity ( Figure 5).…”
Section: Experimental Results and Model Fittingsupporting
confidence: 86%
“…Several recent studies have shown that large performance gains are possible in RFBs through changes in the flow field type, as well as the electrode geometry or morphology. 15,17,18,[20][21][22][23][24] While such reports represent excellent engineering efforts to improve RFB power density, increases in mass transfer rates are rarely quantified, arguably due to insufficient knowledge of relevant transport processes within the ) unless CC License in place (see abstract). ecsdl.org/site/terms_use address.…”
mentioning
confidence: 99%
See 3 more Smart Citations